An Enigmatic Color Change of Urine: Alkaptonuria: Alkaptonuria - Sultana, Azmeri; Rumana, Jubaida; Qader, Abdul; Shahidullah, Shabnam; Rashid, Ismail; Majumder, Rita (Journal of Pediatric Nephrology, 2023)
Alkaptonuria is an exceedingly rare tyrosine metabolism disorder of autosomal recessive inheritance. Only a few instances of it have been observed in Bangladeshi children. Here, we talk about a 2-year-old boy who had dark urine and was later found to have alkaptonuria.